2019
DOI: 10.1038/s41598-019-41100-9
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-derived extracellular vesicles inhibit and revert fibrosis progression in a mouse model of diabetic nephropathy

Abstract: Extracellular vesicles (EVs) that are derived from mesenchymal stromal cells (MSCs) have been shown to reprogram injured cells by activating regenerative processes. We herein investigate the potential therapeutic effect of EVs, shed by human bone marrow MSCs and by human liver stem-like cells (HLSCs), on the progression and reversion of fibrosis in a mouse model of diabetic nephropathy, as induced by streptozotocin. After the development of nephropathy, stem cell-derived EVs were administered weekly to diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(170 citation statements)
references
References 63 publications
(81 reference statements)
10
157
0
3
Order By: Relevance
“…In a mouse model of streptozotocin-induced diabetic nephropathy (DN), multiple (once a week for 4 weeks) intravenous injections of EVs were shown to improve renal function by reversing fibrosis. Array sequencing results showed that the EVs contained high levels of microRNAs, and bioinformatic analyses found that they mainly targeted the biological pathways involved in the profibrotic processes, such as transforming growth factor (TGF)-b, insulin like growth factor 1, EGFR, and PDGFR, which were consistent with the antifibrotic effects exerted by EVs in DN models 77 . In 2016, a clinical trial assessed the safety and therapeutic efficacy of allogeneic hUC-MSC-EVs in the treatment of CKD, including 40 grade III/IV CKD patients, who were randomly divided into two groups.…”
Section: Msc-evs In Kidney Diseasesmentioning
confidence: 60%
“…In a mouse model of streptozotocin-induced diabetic nephropathy (DN), multiple (once a week for 4 weeks) intravenous injections of EVs were shown to improve renal function by reversing fibrosis. Array sequencing results showed that the EVs contained high levels of microRNAs, and bioinformatic analyses found that they mainly targeted the biological pathways involved in the profibrotic processes, such as transforming growth factor (TGF)-b, insulin like growth factor 1, EGFR, and PDGFR, which were consistent with the antifibrotic effects exerted by EVs in DN models 77 . In 2016, a clinical trial assessed the safety and therapeutic efficacy of allogeneic hUC-MSC-EVs in the treatment of CKD, including 40 grade III/IV CKD patients, who were randomly divided into two groups.…”
Section: Msc-evs In Kidney Diseasesmentioning
confidence: 60%
“…MSC-sourced miRNAs, particularly let-7c, targeted pro-fibrotic genes (collagen IVĪ±1, TGF-Ī²1 and TGFĪ²R1) in inflamed kidneys, crucially contributing to the therapeutic effects of MSC-EVs in renal fibrosis and diabetic nephropathy [83][84][85]. In line with these findings were results obtained by Zou and colleagues who indicated that MSC-EV-dependent down-regulation of CXCL1 production was responsible for significantly decreased number of CD68+ macrophages in fibrotic kidneys of MSC-EVs-treated mice [84].…”
Section: Figurementioning
confidence: 99%
“…69 However, the advantages in the use of EVs engineered with Klotho have not been reported yet. In the present study, Klotho was loaded onto fibroblast EVs, a Klotho negative EV source previously described as non-effective in renal repair, 70,71 and the inefficacy of naive EVs in AKI was reverted in parallel with the restoration of its endogenous levels. Moreover, the effect of recombinant Klotho administered alone at a dose comparable with that of uEVs (1 pg/mouse) did not exert any regenerative effect.…”
Section: Discussionmentioning
confidence: 92%